A naturally occurring epiallele associates with leaf senescence and local climate adaptation in Arabidopsis accessions - Li He (Nature Portfolio, 2018)
Epigenetic variation underlies various aspects of phenotypic diversity of plants. Here, He et al show a naturally occurring epiallele controls Arabidopsis leaf senescence by regulating the expression of PHEOPHYTIN PHEOPHORBIDE HYDROLASE (PPH), and is associated with local climate adaptation.